Magnetic Charge and Magnetic Field Distributions in Ferromagnetic Pipe - Xinjing, Huang; Shili, Chen; Shixu, Guo; Wei, Zhao; Shijiu, Jin (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper proposes the equivalent magnetic charge (EMC) method, to analyze the magnetic field presented in ferromagnetic pipe. Distributions of the magnetic charge density on pipes’ surface are calculated, and the magnetic field on several measurement lines is predicted using numerical calculation with several different directions of magnetization. The correctness of the analysis results is then validated by the comparison between the results of the ANSOFT and measurement of the magnetic field inside several actual pipes. With the EMC method, it is of great interest to found that when the magnetization direction changes, the radial and axial magnetic field components inside the pipe will shift accordingly. Moreover, the variation law of magnetic field along the axial retains substantially unaltered, and the magnetic field distribution in the pipe is obviously symmetrical with a plurality of extreme points. As a result, the magnetic field distributes evenly if the pipe is long enough.